Response Gene to Complement 32 in Vascular Diseases - Cui, Xiao-Bing; Chen, Shi-You (Frontiers in Cardiovascular Medicine, 2018)
Response gene to complement 32 (RGC32) is a protein that was identified in rat oligodendrocytes after complement activation. It is expressed in most of the organs and tissues, such as brain, placenta, heart, and the liver. Functionally, RGC32 is involved in various physiological and pathological processes, including cell proliferation, differentiation, fibrosis, metabolic disease, and cancer. Emerging evidences support the roles of RGC32 in vascular diseases. RGC32 promotes injury-induced vascular neointima formation by mediating smooth muscle cell proliferation and migration. Moreover, RGC32 mediates endothelial cell activation and facilitates atherosclerosis development. Its involvement in macrophage phagocytosis and activation as well as T-lymphocyte cell cycle activation also suggests that RGC32 is important for the development and progression of inflammatory vascular diseases. In this mini-review, we provide an overview on the roles of RGC32 in regulating functions of smooth muscle cells, endothelial cells, and immune cells, and discuss their contributions to vascular diseases.